Segmentasi Layanan Jasa Kantor Akuntan Publik Menggunakan Algoritma K-Means Clustering - Hendrawan, Mochamad Bagus; Gunadi, Goldie (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Kantor Akuntan Publik (KAP) XYZ is a business entity that provides audit, accounting, taxation, and financial consulting services to clients. In providing these services, KAP XYZ is required to always deliver the best and most professional service. Therefore, KAP XYZ needs to evaluate the services it has provided. This study aims to perform segmentation of the services offered using the K-Means Clustering method and the Davies-Bouldin Index (DBI) test to find the best cluster. Data processing is carried out using the RapidMiner application. The data used consists of 500 service records to clients, with the k values tested being 3, 4, 5, 6, and 7. The results of the test show the lowest DBI value at k=5 with a score of 0.949, resulting in 5 clusters. Cluster 1 shows the best performance, accounting for 37% of the total services, with 187 services provided to 69 clients. This segmentation provides insights that can be used by KAP management for evaluation and the development of strategies to improve service quality.